Financial Risk Assesment of Post Tsunami 2004 Shrimp Production in Aceh - A U Fitrah; N A Nasution; A Nugroho; A Maulana; Irwan Irwan (UNIVERSITAS ANDALAS, 2020)
This study aims to identify and to measure the impact of financial risks on shrimp farming in relation to post-tsunami 2004 in Aceh and shrimp diseases. Interviews using questionnaires were conducted on 47 shrimp farmers in five shrimp producing regions in Aceh Province. The risks assessments were measured in frequency of the occurence and the severity of the impacts. This study shows that financial risks due to natural disasters and diseases consisted of production and marketsaspects. The deterioration in selling prices and the increase in production costs would affect major impacts as well as having relatively high frequencies.